2019
DOI: 10.1186/s13018-019-1332-5
|View full text |Cite
|
Sign up to set email alerts
|

Should synovectomy be performed in primary total knee arthroplasty for osteoarthritis? A meta-analysis of randomized controlled trials

Abstract: Background During primary total knee arthroplasty (TKA), synovectomy as a part of the procedure has been recommended to relieve pain and inflammation of the synovium, but there is a controversy about it due to increased bleeding. In this meta-analysis, the aim is to answer whether synovectomy should be performed routinely during TKA for symptomatic knee osteoarthritis (KOA). Methods Relevant randomized controlled trials (RCTs) on synovectomy were retrieved through datab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 31 publications
0
5
0
Order By: Relevance
“…[ 5 8 , 12 ] A meta-analysis based on the previous clinical trials has demonstrated that conducting synovectomy in primary TKA for patients with OA does not relieve pain during 1-year follow-up period. [ 14 , 22 ] It was demonstrated in our study that excision or retention of synovium has little effect on postoperative pain post-TKA during a 10-year follow-up period. In addition, based on our findings, the elevation and changes of serum and drainage of IL-6, ESR, and CRP in the two groups were not significantly different.…”
Section: Discussionmentioning
confidence: 68%
See 1 more Smart Citation
“…[ 5 8 , 12 ] A meta-analysis based on the previous clinical trials has demonstrated that conducting synovectomy in primary TKA for patients with OA does not relieve pain during 1-year follow-up period. [ 14 , 22 ] It was demonstrated in our study that excision or retention of synovium has little effect on postoperative pain post-TKA during a 10-year follow-up period. In addition, based on our findings, the elevation and changes of serum and drainage of IL-6, ESR, and CRP in the two groups were not significantly different.…”
Section: Discussionmentioning
confidence: 68%
“…Therefore, several clinical trials have been performed to evaluate the pain, function, and inflammation related to synovectomy in patients with knee OA at short-term follow-up [5–8,12] . A meta-analysis based on the previous clinical trials has demonstrated that conducting synovectomy in primary TKA for patients with OA does not relieve pain during 1-year follow-up period [14,22] . It was demonstrated in our study that excision or retention of synovium has little effect on postoperative pain post-TKA during a 10-year follow-up period.…”
Section: Discussionmentioning
confidence: 99%
“…The worse outcome of these patients could have been be biased by the fact that all of them underwent radical synovectomy. However, a meta-analysis reviewing five RCTs [ 38 ] about concomitant synovectomy during TKA detected no significant difference in clinical and functional KSS or range of motion postoperatively.…”
Section: Discussionmentioning
confidence: 99%
“…At the time of replacement, it is recommended that this be performed uniformly in patients with active synovitis. Synovectomy is possibly not required if the disease is silent and the synovium is not inflamed [13,14].…”
Section: Intraoperative Considerationsmentioning
confidence: 99%